Infection in the Developing Brain: The Role of Unique Systemic Immune Vulnerabilities - Singh, Gabriela; Tucker, Elizabeth W.; Rohlwink, Ursula K. (Frontiers in Neurology, 2022)
Central nervous system (CNS) infections remain a major burden of pediatric disease associated with significant long-term morbidity due to injury to the developing brain. Children are susceptible to various etiologies of central nervous system infection partly because of vulnerabilities in their peripheral immune system. Young children are known to have reduced numbers and functionality of innate and adaptive immune cells, poorer production of immune mediators, impaired responses to inflammatory stimuli and depressed antibody activity in comparison to adults. This has implications not only for their response to pathogen invasion, but also for the development of appropriate vaccines and vaccination strategies. Further, pediatric immune characteristics evolve across the span of childhood into adolescence as their broader physiological and hormonal landscape develop. In addition to intrinsic vulnerabilities, children are subject to external factors that impact their susceptibility to infections, including maternal immunity and exposure, and nutrition. In this review, we summarize the current evidence for immune characteristics across childhood that render children at risk for CNS infection and introduce the link with the CNS through the modulatory role that the brain has on the immune response. This manuscript lays the foundation from which we explore the specifics of infection and inflammation within the CNS and the consequences to the maturing brain in part two of this review series.